The Foundaments of Conservation in Saline and Alkali Soils - Sinha, R L (Journal of Soil and Water Conservation, 2022)
ln the irrigated tracts vast areas of fertile land have gone unproductive or less product- ive due to rise in sub-soil water table and accumulation of salts in the surface, on account of poor drain- age and misuse of irrigation water. It is estimated that there ale about ten million acres of such land at present in India. With increasing irrigation potential under the Five Year Plans the potential danger of soil deterioration on this account is extremely great. This note deals in brief and simple language with the definition of saline and alkali soils, causes, sources and effects of salinity and alkalinity, extent of soil deterio- ration on this account, reclamation methods, fundaments of principles of soil management and outlines of management plan for saline and alkali soils. It is suggested that the problem of saline and alkali soils should be dealt with thoroughly at the Centre and State Govt. level and not left to mediocre cultural prac- tices and resources of an individual person or the Department. It is estimated that by reclamation of these soils the production of country can be stepped upto a great ex- tent besides conserving the water and soil resources of the Nation.